Nonsurgical management of a jones fracture in a collegiate male basketball player - Claypool, A.; Gray, C. (International Journal of Athletic Therapy & Training, 2015)
Jones fractures are often associated with delayed healing, high rates of nonunion, and occurrences of reinjury, such that intramedullary screw fixation is currently regarded as the gold-standard treatment. Nonsurgical treatment should be consid-ered as a potential option when the frac-ture is nondisplaced and the patient does not have a prior history of fifth metatarsal injury. Clinical and radiographic boney union should be present before progressing the patient to sport activity. Patient values should drive plan of care decisions, with support from research evidence and clinician expertise.